Numerical and Experimental-Based Framework for Fuel Cell System Fatigue Analysis in Frequency Domain - Zhe Liu; Mingjie Wang; Pengbo Guo; Dawei Gao; Yunkai Gao (Machines)
New energy vehicles have emerged as a prominent focus in the automotive industry. This study develops a comprehensive modeling specification for fuel cell systems in new energy vehicles and establishes a framework for fatigue life analysis in the frequency domain. First, a finite element model of the fuel cell system was created in accordance with established standards, followed by grid convergence analysis and grid quality correction to enhance model accuracy. Next, random vibration analysis was performed to determine the root mean square (RMS) stress distribution of the fixed plate assembly in a random vibration environment, and the results were validated through experimental tests. Finally, Miner’s linear cumulative damage rule and the rainflow distribution model for random processes were applied to predict the fatigue life of the fixed plate assembly and connecting bolts. Critical locations for potential structural fatigue were identified, and the simulation results were corroborated through fatigue testing. The findings validate the accuracy of the proposed fatigue analysis framework and offer valuable insights for the continued development of fuel cell systems.